2016
DOI: 10.1038/srep38376
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a gastric cancer subline with high metastatic potential using a novel microfluidic system

Abstract: Metastasis is an important hallmark of malignant tumors. In this study, we developed a microfluidic system to screen highly metastatic sublines via differential resolution of cell invasiveness. The system was composed of a PDMS-glass device connected with a syringe pump and a Petri dish. To facilitate the selection process, a long-term cell invasion driving force based on a chemotactic factor gradient was created using the Petri dish-based liquid supply pattern, and the invasive cells were collected for round-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 29 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…Our previous study has confirmed gastric cancer cells that injected in the armpits has capability of spontaneous metastasis [ 19 ]. To determine the anti-tumor function of miR-135a, we inject control and miR-135a overexpressing cells into the bilateral axillary of BALB/c nude mice respectively.…”
Section: Resultsmentioning
confidence: 82%
“…Our previous study has confirmed gastric cancer cells that injected in the armpits has capability of spontaneous metastasis [ 19 ]. To determine the anti-tumor function of miR-135a, we inject control and miR-135a overexpressing cells into the bilateral axillary of BALB/c nude mice respectively.…”
Section: Resultsmentioning
confidence: 82%
“…Recently, some metastasis‐on‐a‐chip (MoC) devices have been described for the analysis of these phenomena, which differ in the origin of the cancer cells, the architecture of the chip or the composition of the cellular microenvironment. [ 147,148 ] Some of these devices use SGC‐7901 human gastric cancer cells [ 149 ] or NPC‐BM1 nasopharyngeal carcinoma cancer cells, [ 150 ] with high metastatic capacity to obtain representative results. In the first of these, a microfluidic system was developed to detect highly metastatic sublines through the differential resolution of cell invasion.…”
Section: Study Models For Metastasis Researchmentioning
confidence: 99%
“…In conclusion, this microfluidic system proved to be a very effective tool for selecting highly metastatic sublines, and this SGC‐7901/B2 cell subline could serve as a potential model for tumor metastasis research. [ 149 ]…”
Section: Study Models For Metastasis Researchmentioning
confidence: 99%
See 1 more Smart Citation